2014
DOI: 10.4103/2225-4110.128897
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Chrysanthemum morifolium Enhances the Antimelanogenic and Antioxidative Activities of the Mixture of Soy Peptide and Collagen Peptide

Abstract: The possible synergistic effect between the aqueous extract of Chrysanthemum morifolium (菊花 Jú Huā) (AECM) and the peptide mixture (PM) containing soy peptide and collagen peptide was investigated in an ultraviolet (UV) irradiation–induced skin damage mouse model. The irradiated mice were treated with the PM or PM + AECM (containing PM and AECM), respectively. Both PM and PM + AECM groups displayed an apparent photoprotective effect on the UV-irradiated skin damage of mice. Histological evaluation demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Our previous study confirmed that soy peptide had synergistic antioxidant activities with collagen peptide [10]. The mixture of soy peptide and collagen peptide showed good antioxidant activity in the senescent mouse model [5].…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…Our previous study confirmed that soy peptide had synergistic antioxidant activities with collagen peptide [10]. The mixture of soy peptide and collagen peptide showed good antioxidant activity in the senescent mouse model [5].…”
Section: Introductionmentioning
confidence: 55%
“…UV radiation is an important causative factor in melasma, inducing ROS formation and melanin pigment biosynthesis in the skin [19,20]. Our previous study demonstrated that the CP exerted photoprotective and antioxidant activity both in UV-induced mice model and in vitro study [10]. The number and size of DOPA-positive melanocytes were found to be significantly decreased in the group treated with CP against UBV-induced skin response, suggesting CP inhibited UVB-induced pigmentation because of its antioxidant and tyrosinase inhibitory effects [10].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Its mechanisms were at least partially associated with the modulations of TLR4 signaling pathways 55 . The oral intake of peptide mixture and the aqueous extract of Chrysanthemum Gui et al, 2014 morifolium had synergistic antimelanogenic and antioxidative effects in UV-irradiated mice 56 . According to the literature survey, it can be concluded that fifty compounds were Sassi et al, 2014 identified from essential oils of the leaves, stems and roots of Chrysanthemum trifurcatum (Desf.)…”
Section: Key Findings Referencementioning
confidence: 99%